Antioxidative response of Phanerochaete chrysosporium against silver nanoparticle-induced toxicity and its potential mechanism - Huang, Zhenzhen; He, Kai; Song, Zhongxian; Zeng, Guangming; Chen, Anwei; Yuan, Lei; Li, Hui; Hu, Liang; Guo, Zhi; Chen, Guiqiu (Chemosphere (Oxford), 2018)
Antioxidative response of Phanerochaete chrysosporium induced by silver nanoparticles (AgNPs) and their toxicity mechanisms were comprehensively investigated in a complex system with 2,4-dichlorophenol (2,4-DCP) and Ag+. Malondialdehyde content was elevated by 2,4-DCP, AgNPs, and/or Ag+ in concentration- and time-dependent manners within 24 h, indicating an increase in lipid peroxidation. However, beyond 48 h of exposure, lipid peroxidation was alleviated by upregulation of intracellular protein production and enhancement in the activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD). Comparatively, POD played more major roles in cell protection against oxidative damage. Furthermore, the dynamic change in reactive oxygen species (ROS) level was parallel to that of oxidized glutathione (GSSG), and ROS levels correlated well with GSSG contents (R2 = 0.953) after exposure to AgNPs for 24 h. This finding suggested that elimination of oxidative stress resulted in depletion of reduced glutathione. Coupled with the analyses of anoxidative responses of P. chrysosporium under the single and combined treatments of AgNPs and Ag+, HAADF-STEM, SEM, and EDX demonstrated that AgNP-induced cytotoxicity could originate from the original AgNPs, rather than dissolved Ag+ or the biosynthesized AgNPs. [Display omitted] •Lipid peroxidation was alleviated via enhancement of SOD, CAT, and POD activities.•POD played a predominant role in effective protection against chronic cell damage.•Suppression of ROS production was closely related to the depletion of GSH at 24 h.•HAADF-STEM and EDX analyses revealed particle-specific toxicity mechanism of AgNPs.